EFEKTIVITAS METODE PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Nadia Vinieta Setia; Patrick Vallerio; Putri Wulandari; Lia Handayani; Khilfa Yahya (PROSIDING SERINA, 2021)
Online learning is one of the efforts made by the government to reduce the spread of the Covid-19 virus. In accordance with the circular letter of the Ministry of Education and Culture No. 4 of 2020 concerning the implementation of education policies in the emergency period of the spread of Coronavirus Disease (Covid-19) related to the learning process states that learning from home through online or distance learning is carried out to provide meaningful learning for students. Of course, this brings various impacts, both directly and indirectly, on the students themselves. Based on the research results, the unpreparedness of lecturers and students in using online learning platforms is one of the problems that can hinder the effectiveness of online learning. Pembelajaran daring merupakan salah satu upaya yang dilakukan pemerintah untuk mengurangi penyebaran virus Covid-19. Sesuai dengan surat edaran Kementerian Pendidikan dan Kebudayaan No. 4 tahun 2020 tentang pelaksanaan kebijakan pendidikan dalam masa darurat penyebaran Coronavirus Disease (Covid-19) terkait proses belajar menyatakan bahwa belajar dari rumah melalui pembelajaran daring atau jarak jauh dilaksanakan untuk memberikan pembelajaran yang bermakna bagi siswa. Tentunya hal ini membawa berbagai dampak baik secara langsung maupun tidak langsung terhadap para pelajar itu sendiri. Berdasarkan hasil penelitian, ketidaksiapan dosen maupun mahasiswa dalam menggunakan platform pembelajaran daring menjadi salah satu masalah yang dapat menghambat efektivitas pembelajaran daring.